2011
DOI: 10.1111/j.1365-2850.2011.01752.x
|View full text |Cite
|
Sign up to set email alerts
|

Acute mental health nurses: comprehensive practitioners or specialist therapists?

Abstract: This paper examines the aids and barriers to implementing the psychosocial interventions (PSI) which trainees learned on two teaching modules. The main purpose of the modules is to teach trainees PSI to help them be more effective in their care of patients with severe mental illness. The trainees were qualified nurses working in acute mental health wards in various London hospitals. PSI has been found to be helpful for patients with psychotic symptoms in community contexts. In this study, the implementation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 11 publications
(12 reference statements)
0
4
0
Order By: Relevance
“…Also, ongoing supervision in PSI needs to be provided by academic staff and trainees need to liaise more closely with consultants regarding patient discharge [3] . In order for acute inpatient mental health wards to achieve their full therapeutic potential these factors will need to be addressed so that skills learned on such modules can be utilised effectively in the future.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, ongoing supervision in PSI needs to be provided by academic staff and trainees need to liaise more closely with consultants regarding patient discharge [3] . In order for acute inpatient mental health wards to achieve their full therapeutic potential these factors will need to be addressed so that skills learned on such modules can be utilised effectively in the future.…”
Section: Resultsmentioning
confidence: 99%
“…PSI skills such as the psychoeducation mentioned above have been used by mental health nurses in community settings for many years and have been well evaluated [2] but the evidence is relatively sparse for acute inpatient wards. Implementing PSI alongside medication in inpatient settings could improve the patient's quality of life here too, and perhaps reduce length of stay [3] . Given the pressure on acute beds, mental health service providers welcome interventions that can result in a reduction in length of stay.…”
Section: Introductionmentioning
confidence: 99%
“…, Fourie et al . , Mathers ). Furthermore, the complexity of the decision to admit or not admit a person with mental illness as an involuntary patient is well realized (Anderson & Eppard , Engleman et al .…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Brennan et al, (2006) revealed that lack of knowledge of their role within the health team and in the attainment of organisational goals and lack of autonomy constitute barriers to provision of psychiatric nursing care. Other personal barriers to provision of psychiatric care are as follows: lack of appropriate and specific training and education, inability to use acquired skills due to time constraints and huge workload, and allocation to inferior roles within the psychiatric health team (Mathers, 2012;Wong, 2014;McAllister and Moyle, 2008). Other personal barriers to provision of psychiatric nursing care highlighted in literature in high-income economies include: indifferent attitudes of some psychiatric nurses towards provision of care, lack of interest in provision of psychiatric care among some psychiatric nurses, low morale and low selfesteem/confidence, and frustration from managers over perceived under-performance of their subordinates (Wong, 2014;Brennan et al, 2006;Chevalier et al, 2006;Jelinek et al, 2011).…”
Section: Barriers To Provision Of Psychiatric Nursing Care In High-inmentioning
confidence: 99%